Acute kidney injury after benign prostate hypertrophy surgery - Herrera Añazco, Percy (2012)
Objective: To assess the development of acute renal failure in patients undergoing elective surgery for benign prostate hypertrophy. Material y Method: The study was performed in patients from the Urology Service in 2 de Mayo National Hospital from September 22011 to February 2012. The AKIN definition was used for acute renal failure and data was collected from clinical records. The description used means, standard deviations, percentages, and rates. In order to find an association between the occurrences of acute renal failure categorical variables, bivariate and multivariate logistic regression tests were used. Results: One hundred and twenty three patients were assessed; their average age was 69,29 ± 8,27 years. Hypertension was reported in 23,58% and diabetes mellitus was found in 8,94%. Urinary outlet obstruction was found in 4,07%. Their average weight was 66,94 ± 14,2 Kg, hemoglobin concentration was 13,58 ± 1,7 g/dL, mean creatinine value prior to surgery was 0,93 ± 0,58 mg/dL, and their glomerular filtration rate (GFR) calculated using the MDRD formula was 99,16 ± 30,88 mL/min. GFR values below 60 mL/min prior to surgery were found in 3,25% of patients. When creatinina levels were used for diagnosis, 1,63 % of patients had a diagnosis of acute renal failure, and the figure climbed to 6,5% when urinary output was used for defining this condition. Consequently, 8,13% of all patients had acute renal failure, all of them were stage 1. No fatalities were reported in patients with acute renal failure, and there was no association between the occurrence of acute renal failure and the categorical variables assessed. Conclusions: Post surgery acute renal failure was found in 8,13% of patients undergoing elective surgery for benign prostate hypertrophy, and there was no increase of in-hospital mortality in these subjects.